Long-term color stability of orthodontic adhesives after exposure to different staining agents - Thiago Vinícius Pavelski; Daniel Gheur Tocolini; Gisele Maria Correr; Leonardo Fernandes da Cunha; Carla Castiglia Gonzaga (Wolters Kluwer Medknow Publications, 2019)
Context: The aims of this study were (i) to evaluate the color stability of two orthodontic adhesives and (ii) to evaluate the color stability of enamel and ceramic brackets bonded with orthodontic adhesives after exposure to different staining agents. Materials and Methods: Disks were prepared with two orthodontic adhesives (Transbond and Enlight). Color stability evaluation was performed with a spectrophotometer using CIELab parameters. The specimens were divided into four groups and immersed in the following staining agents (n = 5): distilled water (control), coffee, red wine, and cola soft drink, for 1 h/day for 120 days. Twenty molar crowns were also used. The baseline color of enamel was obtained and ceramic brackets were bonded with the orthodontic adhesives. The enamel specimens were divided into four groups and immersed in the same staining agents. After 120 days, another color reading with the brackets in position was taken. The brackets were then removed and the enamel color was again evaluated. Color difference (ΔE) in different time periods was determined and the data were analyzed by ANOVA and Tukey's test (α = 5%). Results: Transbond showed lower ΔE than Enlight. Water, cola, and coffee had the lowest ΔE values. Immersion in wine showed the highest ΔE values. For time, the lower ΔE values were found for 24 h and 7 days. Storage times of 60, 90, and 120 days showed the highest ΔE values. ΔE for enamel showed significant differences only for time. Conclusion: Adhesive, staining agents, and storage time influenced the color stability of orthodontic adhesives.